2010
DOI: 10.1159/000277598
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Axial Penile Rigidity in Objective Evaluation of Erection Quality in Patients with Erectile Dysfunction – Comparison with Radial Rigidity

Abstract: Introduction: The aim of this prospective study was to evaluate the usefulness of measurement of axial penile rigidity, compared with radial penile rigidity. Patients and Methods: Twenty-two patients, aged 21–75 years old (a mean of 50), with erectile dysfunction underwent axial penile rigidity measurements by the digital inflection rigidometer (DIR) as well as radial penile rigidity measurements by the RigiScan Plus during intracavernous pharmacological erection testing. Results: A significant correlation was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…However, some experts have questioned NPT's accuracy, reliability, and usefulness in differential diagnosis. 8,9 In this study, our data have shown that the ED diagnosis was significantly associated with NPT results, validating the guideline in general. However, our study also identified 3 special cases in which the patients had normal NPT responses but still were diagnosed with organic ED.…”
Section: Commentsupporting
confidence: 81%
“…However, some experts have questioned NPT's accuracy, reliability, and usefulness in differential diagnosis. 8,9 In this study, our data have shown that the ED diagnosis was significantly associated with NPT results, validating the guideline in general. However, our study also identified 3 special cases in which the patients had normal NPT responses but still were diagnosed with organic ED.…”
Section: Commentsupporting
confidence: 81%
“…For example, RigiScan is the most widely utilized device for measuring penile radial rigidity15, but this device does not directly determine axial rigidity 3,6,7. On the contrast, Digital Inflexion Rigidometer is a useful device for measuring penile axial rigidity3,8,9, but it does not directly determine radial rigidity. Complete erection rigidity assessment needs a combinatorial use of RigiScan and Digital Inflexion Rigidometer, which increased the cost and inconvenience.…”
Section: Introductionmentioning
confidence: 99%
“…The reliability of this parameter, however, was hampered by its inconsistency and a wide margin of error [15]. On the other hand, although the concept of nocturnal penile tumescence recording as a diagnostic tool for ED was first reported in 1965 [30], it was not clinically applicable till the appearance of RigiScan in 1970, which enabled a safe and effective measurement of penile erection during sleep [12,13]. Through measuring the tumescence and rigidity over the base and tip of the penis, the equipment has been validated in ED diagnosis with applicability extended to both sleeping [25] and awake conditions using visual sexual stimulation (VSS) [28].…”
Section: Discussionmentioning
confidence: 99%
“…All acquired data were digitized and stored and analyzed with microcomputer in the equipment up to 10 hours. The data can be expressed as data sheets or charts through connection to an external computer [12,13].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation